Fish and seafood consumption during pregnancy and the risk of asthma and allergic rhinitis in childhood: a pooled analysis of 18 European and US birth cohorts. (27th February 2017) - Stratakis, Nikos; Roumeliotaki, Theano; Oken, Emily; Ballester, Ferran; Barros, Henrique; Basterrechea, Mikel; Cordier, Sylvaine; de Groot, Renate; den Dekker, Herman T; Duijts, Liesbeth; Eggesbø, Merete; Pia Fantini, Maria; et al.
Abstract: Background: It has been suggested that prenatal exposure to n-3 long-chain fatty acids protects against asthma and other allergy-related diseases later in childhood. The extent to which fish intake in pregnancy protects against child asthma and rhinitis symptoms remains unclear. We aimed to assess whether fish and seafood consumption in pregnancy is associated with childhood wheeze, asthma and allergic rhinitis. Methods: We pooled individual data from 60 774 mother-child pairs participating in 18 European and US birth cohort studies. Information on wheeze, asthma and allergic rhinitis prevalence was collected using validated questionnaires. The time periods of interest were: infancy (0-2 years), preschool age (3-4 years), and school age (5-8 years). We used multivariable generalized models to assess associations of fish and seafood (other than fish) consumption during pregnancy with child respiratory outcomes in cohort-specific analyses, with subsequent random-effects meta-analyses. Results: The median fish consumption during pregnancy ranged from 0.44 times/week in The Netherlands to 4.46 times/week in Spain. Maternal fish intake during pregnancy was not associated with offspring wheeze symptoms in any age group nor with the risk of child asthma [adjusted meta-analysis relative risk (RR) per 1-time/week = 1.01, 95% confidence interval 0.97-1.05)] and allergic rhinitis at school age (RR = 1.01, 0.99-1.03). These results were consistently found in further analyses by type of fish and seafood consumption and in sensitivity analyses. Conclusion: We found no evidence supporting a protective association of fish and seafood consumption during pregnancy with offspring symptoms of wheeze, asthma and allergic rhinitis from infancy to mid childhood.